Urgensi Hak Buruh dalam Kebijakan Pengupahan - Quri’syaich Say Mandari; Ernu Widodo; Fathul Hamdani (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2025)
Every worker as an Indonesian citizen has the desire to get a decent and prosperous life and get a decent job. A prosperous life can be achieved through the implementation of obligations as workers, the mandate is contained in Article 27 paragraph (1) of the 1945 Constitution of the Republic of Indonesia which states: "Every citizen has the right to work and a decent livelihood for humanity." And in Article 28D paragraph (2): "Everyone has the right to work and receive fair and proper remuneration and treatment in employment relations." The legal issue of this normative legal research: How are labor rights regulated? What is the wage policy for workers? The regulation of labor rights in the Job Creation Law, which is regulated in Law Number 6 of 2023 concerning Government Regulation in Lieu of Law No. 2 of 2022 concerning Job Creation into Law, includes several important aspects that aim to provide certainty and protection for workers. The Job Creation Law stipulates certainty regarding rights and obligations for workers and companies, including arrangements regarding wages, working hours, and leave. The arrangement is expected to build a harmonious working relationship and in accordance with applicable laws and regulations. Wage policies, especially regulated in the Labor Law, have the purpose of protecting workers' rights and ensuring welfare. That regarding wage policies for workers in the form of minimum wages, wage components, protection of workers' rights and labor welfare.